Essix restoration: a novel approach for transitional teeth replacement. (23rd April 2014) - Patel, Avani; Prajapati, Paranjay; Sethuraman, Rajesh; Patel, Jayanti R
Summary: Loss of teeth is a distressing situation. The patient may cultivate feeling of loss of an organ on loss of teeth. Especially when anterior teeth are lost appearance of the patient is compromised with altered pronunciation. This is a really embarrassing situation for people working as news readers, social workers, marketing executives, theatre artists or persons whose presentation in front of people is important as part of their work. Replacement of missing teeth immediately after loss is not possible always due to local and systemic physiological factors, age, pathological factors and unfavourable condition of soft tissue in a particular area. Various means are available for transitional replacement of teeth which may or may not require adjacent teeth preparation. Essix restoration is easy to fabricate and use the restoration option with great aesthetic value.